Argamassas de cimento portland aditivado com partículas de calcário mineral e partículas ultrafinas de carbonato de cálcio : morfologia, propriedades mecânicas e durabilidade - Bartley, Bertilia Lauralee (2016)
This study concentrates on the use of micro particles of limestone (CMV) and nano scale calcium carbonate (Np-CaCO3) in Portland cement (OPC) substitution in order to evaluate the influence in hydration reactions, microstructural morphology, mechanical properties and the durability of cement pastes and mortar. Specimens where characterized by X-ray diffraction, scanning electron microscopy, uniaxial compression, micro hardness and thermo gravimetric analysis. Atypical morphologies of calcium silicate hydrate (C-S-H) were observed in the pastes in the presence of high amount of Np-CaCO3. The results indicate that the Np-CaCO3 is reactive; accelerating early age C-S-H formation. Based on the morphological and mechanical properties, a synergetic effect was observed by the combined addition of CMV with low amounts of Np-CaCO3. Compressive strength results of the mortars are compatible with the standard requisite of the American Society of Testing Materials (ASTM). The durability of the mortars was evaluated by expositional aging methods in natural and laboratory environment for 6 months. The mechanical properties and durability of the composite cement mortars are competitive with results obtained by the reference mortars. By overall analysis of the results, it was concluded that OPC substitution of 10-30 wt.% CMV, when combined with controlled amount of Np-CaCO3 prove viable.